Electricity Production, Economic Growth and Employment Nexus in Sudan: A cointegration Approach - Awad, Atif; Yossof, Ishak (International Journal of Energy Economics and Policy, 2015)
The present study examines the relationship between electricity production, economic growth and employment in Sudan between 1980 and 2013 by using cointegration and causality techniques. We use the Wald test to determine the direction of the causality relationship between the variables. The results show that there is a long run relationship between the variables. The causality relationship test detects the existence of bidirectional relationship between energy generation and economic growth in the short run. The causality analysis also detects the existence of long as well as strong long run bidirectional relationship between each pair of the variables. Overall, the results suggest that even in short run, decrease in the electricity will lead to fall in the economic growth, and vice versa.. Thus, the results lend support to the recent effort by Sudan's government in the expansion of electricity production, since it has significant impact on the country's economic development. Keywords: economic growth; electricity production; employment JEL Classifications: J21; O10; Q43